Tindak Pidana Pemalsuan Surat Dalam Perspektif Hukum Pidana Indonesia - Tasripin, Ipin; Heliany, Ina (FOCUS, 2026)
The criminal act of document forgery is an unlawful act because it can cause harm to others and undermine public trust in the validity of documents. Forgery occurs when someone intentionally creates, modifies, or imitates a document to make it appear as if it is authentic and issued by an authorized party, when in fact it is not. The formulation in this research is how criminal law regulates the crime of document forgery in Indonesia and how the law is applied by judges in sentencing perpetrators of document forgery, as seen in the Subang District Court Decision Number 60/Pid.B/2024/PN Sng. This research is normative legal research, a method that focuses on analyzing legal regulations, legal principles, and prevailing legal doctrines. The researcher uses legal sources such as statutes, regulations, court decisions, and legal literature to understand and interpret existing law. The findings show that in criminal law, every form of involvement in a criminal act entails its own legal responsibility. In the case of document forgery committed by the defendant DP bin alm R, the witness Dedi Priyanto who gave the order should also have been held criminally liable as the person who instructed the crime, in accordance with Article 55 paragraph (1) point 1 of the Indonesian Criminal Code (KUHP). This reflects the principle that not only the direct perpetrator, but all parties who play an active role in the crime must be held legally accountable. In Decision Number 60/Pid.B/2024/PN Sng, the Panel of Judges concluded that the elements of Article 263 paragraph (1) of the Criminal Code concerning document forgery were proven against Defendant DP bin alm R. The defendant made an invoice containing false information to mislead the company into believing that a debt had been paid off. For his actions, he was sentenced to five months’ imprisonment and remained in detention, with court costs amounting to Rp. 5,000. The decision took into account the principles of legality, legal certainty, and proportionality, as well as considering the defendant’s polite demeanor as a mitigating factor.